Efektivitas Metode Bom (Breastcare, Oxytocin Massage, Marmet Technique) Terhadap Produksi Asi Pada Ibu Post Partum Di Klinik Umum Mitra Bunda Kota Palu Sulawesi Tengah - Maria Vita Insani; Reni Yuli Astutik; Riza Tsalatsatul Mufida; Mifthakur Rohmah (Journal of Health Science Community, 2025)
Problem which often occurs in postpartum mother where is breast milk production so little that it is unable to meet needs baby nutrition. This is because due to lack of knowledge about breast care, oxytocin massage and marmet technique. The purpose of this study was to determine the effectiveness of the BOM method ( Breastcare, Oxytocin Massage, Marmet Technique ) on breast milk production. in postpartum mothers at the Mitra Bunda General Clinic, Palu City, Central Sulawesi.The design of this study was a posttest without control group design with a quasi-experimental approach . Respondents were taken using a purposive sampling technique that met the inclusion and exclusion criteria with a sample of 30 people. The independent variable is the BOM method ( Breastcare, Oxytocin Massage, Marmet Technique ) and the dependent variable is breast milk production in postpartum mothers. The results of statistical tests using the Wilcoxon test . The results of the study showed that breast milk production in postpartum mothers before the BOM method ( Breastcare, Oxytocin Massage, Marmet Technique ) was known to almost all respondents, 26 (87%) in the category of no increase in breast milk production. and after treatment it was known that almost all respondents 28 (93%) were in the category of increased breast milk production. The results of the data analysis show that the significance level is 0.000 < α = 0.05 so that H0 is rejected and H1 is accepted, thus the BOM method ( breastcare, oxytocin massage, marmet technique ) effective for breast milk production in postpartum mothers. Based on the results of the study, it was concluded that oxytocin massage, breast care and marmet techniques are alternatives to increase breast milk production. It is hoped that midwives will always socialize breast massage, oxytocin massage and marmet techniques to mothers during pregnancy so that they can increase mothers’ knowledge in increasing breast milk production.